2000
DOI: 10.1016/s0735-1097(00)00521-0
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic outcomes of noncardiac surgery soon after coronary stenting

Abstract: Postponing elective noncardiac surgery for two to four weeks after coronary stenting should permit completion of the mandatory antiplatelet regimen, thereby reducing the risk of stent thrombosis and bleeding complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
326
2
26

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(360 citation statements)
references
References 18 publications
6
326
2
26
Order By: Relevance
“…Prior coronary stenting is a well-established risk factor associated with major adverse cardiac events. 1,[16][17][18][19] More recently, however, Holcomb and colleagues demonstrated that the incremental risk of cardiac complications significantly decreases when surgery is performed more than 6 months following coronary stenting: the incremental risk of cardiac complications stabilizes at 1% beyond 6 months following coronary stenting. 20 Although NSQIP excludes those with prior percutaneous coronary intervention within 6 months of hepatectomy, we still found that those with history prior PCI (>6 months before the liver resection) had a cardiac complication rate of 6.4% as well as a three-fold increase risk of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Prior coronary stenting is a well-established risk factor associated with major adverse cardiac events. 1,[16][17][18][19] More recently, however, Holcomb and colleagues demonstrated that the incremental risk of cardiac complications significantly decreases when surgery is performed more than 6 months following coronary stenting: the incremental risk of cardiac complications stabilizes at 1% beyond 6 months following coronary stenting. 20 Although NSQIP excludes those with prior percutaneous coronary intervention within 6 months of hepatectomy, we still found that those with history prior PCI (>6 months before the liver resection) had a cardiac complication rate of 6.4% as well as a three-fold increase risk of cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Stents are expected to provide protection against postoperative AMI in noncardiac surgeries [14]; however, patients with AMI + a stent had a high risk of post-TKA AMI within 1 year of its placement. Previous studies to evaluate the risk of postoperative catastrophic events in the patients with a stent have reported variable recommendations about timing for surgery [10,19,24]. The high risk has been attributed to the discontinuation of antiplatelet drugs before the surgery [10,19,24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies to evaluate the risk of postoperative catastrophic events in the patients with a stent have reported variable recommendations about timing for surgery [10,19,24]. The high risk has been attributed to the discontinuation of antiplatelet drugs before the surgery [10,19,24]. This high risk also suggests that the timing of the TKA for some patients with AMI + stent did not comply with the timing (after 6 months) recommended by ACC/AHA for patients after percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…61 Kaluza et al showed that non-cardiac surgery soon after BMS placement (often requiring aspirin withdrawal) was linked to a very high rate of adverse events. 62 A second report describes a patient who simultaneously received a BMS and a DES stent. 63 Twelve weeks later, the patient underwent knee surgery.…”
Section: Risk Of Coronary Events If Antiplatelet Medications Are Discmentioning
confidence: 99%